Study of the phase-evolution mechanism of an Fe-Se system at the nanoscale: optimization of synthesis conditions for the isolation of pure phases and their controlled growth - Ghalawat, Monika; Poddar, Pankaj (Langmuir, 2020)
The iron selenide (Fe-Se) family of nanoparticles (FexSey-where x/y ranges from 1:2 to 1:1) has been fabricated by a thermal decomposition method. The control over solution chemistry has been developed by intensively investigating the effect of reaction parameters by means of wide-angle X-ray scattering, leading to the rich insights into the phase-evolution mechanism of the Fe-Se system. The phase transformation followed the FeSe2 -> Fe3Se4 -> Fe7Se8 -> FeSe sequence in the temperature range of 110-300 degrees C. The deep mechanistic insight helped in the identification of optimized conditions needed to crystallize the individual phase of the Fe-Se system as well as control of the morphology, crystalline phase purity, and thermal stability of the obtained Fe-Se nanoparticles.

Study of growth kinetics of Fe3Se4 nanocrystallites and the influence of size and shape tunability on their magnetic properties - Ghalawat, Monika; Poddar, Pankaj (Journal of Physical Chemistry C, 2021)
Crystalline iron selenide (Fe3Se4) nanoparticles (NPs) present a useful model system for a fundamental understanding of magnetism apart from having potential applications in permanent-magnet-related technologies. Despite significant advancements in understanding of the nucleation and growth processes, control over size and shape tunability is nontrivial, especially for the transition metal chalcogenides (TMC). The Wulff theorem states that if a crystal can grow purely under thermodynamic control of parameters then it will adopt the shape determined by the surface-energy minimization, i.e., the surface energy minimization will drive the growth of each crystalline facet. However, the known or unknown, controllable or uncontrollable parameters of a typical reaction which makes kinetic growth more art than science, depending upon whether we understand them or not. There is hardly any study based on existing models and theories to explain the TMC morphology evolution. In this work, there is a conscious effort to know, understand, and control the individual role of various reaction pathways on the shape and size of the Fe3Se4 nanocrystals. A qualitative growth mechanism is proposed based on the diffusion and reaction processes. Furthermore, the influence of shape/size on the magnetic parameters such as coercivity (H-C), magnetization (M-60kOe), effective magnetic anisotropy constant (K-eff), energy product (BHmax), and average blocking temperature (T-B) is investigated for Fe3Se4 NPs. After diving deeper into the science of crystal growth, our insight provides valuable guidance on experimental conditions for the synthesis of Fe3Se4 NPs with tunable sizes/shapes which for the first time can be extended to most TMCs.

Self-powered wearable breath sensor cum nanogenerator using AuNR-rGO-PVDF nanocomposite - Bang, Amruta D.; Ghalawat, Monika; Poddar, Pankaj; Kulkarni, Sulabha K.; Adhyapak, Parag V. (IEEE Sensors Journal, 2023)
Breathing is the most important function of living being. It is well known that breath contains 90% humidity along with various gases and volatile organic compounds (VOCs). These gases are released during various metabolic activities in the body. These gases present in the breath can act as biomarkers to showcase healthiness or abnormalities in the body. Therefore, breath sensors are the need of time to detect diseases at early stages and in noninvasive way. Herein, we report, simple breath sensor using Au nanorods (AuNRs) and its nanocomposite with reduced graphene oxide (rGO) and polyvinylidene fluoride (PVDF). The nanocomposites system is designed in such a way that each component has its advantages for breath sensing. Here, AuNR being a good humidity sensitive material detects the breath efficiently. The ss phased PVDF being a very good ferroelectric material, contributes for voltage generation during sensing and enables the device to be self powered. The highly conducting rGO increases the sensitivity and voltage generation by facilitating the electron transport in the nanocomposite system. The nanocomposite was optimized with respect to PVDF, rGO and Au concentration. The as-synthesized materials were characterized by physiochemical characterization techniques such as field emission scanning electron microscopy (FESEM), X-ray diffraction analysis (XRD), UV-Visible spectroscopy, Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS). The ss phase formation of the PVDF was confirmed from the XRD peak at 20.41 degrees. SEM results revealed that AuNR have length 15-20 nm and aspect ratio similar to 3-4. Breath sensing tests were carried out for as synthesized nanocomposite material. The nanocomposite exhibited high sensitivity towards breath and generated the voltage of similar to 0.7 V within 0.8 s.
Keywords: Au nanorods (AuNRs); breath analyzer; breath sensor; nanogenerator